Potential of Cation Exchange Resin as a Carrier for Anaerobic Consortia in Biohydrogen Fermentation - Geng, Hui; Xu, Ying; Liu, Rui; Yang, Dianhai; Dai, Xiaohu (Fermentation (Basel), 2024)
Cation exchange resin (CER) has been reported to promote sludge fermentation. However, previous studies have typically focused on the effects of CER on sludge properties to enhance fermentation, and the role of CER as a biocarrier for anaerobic consortia during fermentation has been overlooked. Thus, in this study, the potential of gel-type and macro-reticular type CERs to serve as biocarriers in fermentation was investigated. A significant number of anaerobes appeared to be attached to the surfaces of CER during 2-day fermentation. However, an extended fermentation time negatively affected the attachment of anaerobic consortia, suggesting that CER may be a suitable carrier for short-term fermentation processes, such as biohydrogen fermentation. Electrochemical analyses revealed that the electron transfer capacities of CER with attached anaerobes were enhanced after both 2-day and 28-day fermentation periods, with the macro-reticular type CER exhibiting higher electron transfer capacity than the gel-type CER. Fermentation experiments using mixing model substrates with macro-reticular and gel-type CERs with attached anaerobes showed that the macro-reticular type CER was more beneficial for biohydrogen fermentation than the gel-type CER. Further analyses of microbial communities revealed that hydrogen-producing bacteria (i.e., Caloramator, unclassified_f_Caloramatoraceace, and Sporanaerobacter) were more likely to adhere to the macro-reticular type CERs. This outcome confirmed that macro-reticular type CERs have significant potential as a carrier for anaerobic consortia to promote the generation of hydrogen and volatile fatty acids. These findings are expected to provide a reference for using materials as biocarriers to enhance the biohydrogen fermentation of sludge.